Can we treat ab initio atomic charges and bond orders as conformation-independent electronic structure descriptors?. Issue 78 (8th August 2016) - Nikolaienko, T. Yu.; Bulavin, L. A.; Hovorun, D. M.
Abstract : It is shown that atomic charges and bond orders of 2′-deoxycytidine depend on the molecule conformation. Abstract : Chemically meaningful descriptors of molecular electronic structure which can be calculated from the results of ab initio calculations in a well-defined manner play an important role in establishing a fundamental link between chemistry and physics. Bond orders (BOs) and effective atomic charges, both expressible in terms of the electron density matrix and the overlap matrix, comprise examples of such descriptors. In the present paper the dependence of BOs (calculated by NPA-Wiberg, Natiello–Medrano and Mayer methods) and atomic charges (calculated by Natural Population Analysis (NPA) and Löwdin schemes) on the conformation of DNA deoxyribonucleoside 2′-deoxycytidine is investigated. Strong correlations between the studied descriptors of molecular structure calculated by different methods are revealed and discussed. The atoms and bonds of 2′-deoxycytidine exhibiting the most pronounced dependence of their effective charges and bond orders on the conformation are identified.